Influence of farmers crop managemnt practices on Striga hermonthica infestation and grain yield of maize (Zea mays L.) in the savanna zones of northeast Nigeria - Dugje, I.Y.; Kamara, A.Y.; Omoigui, L.O. (2008)
The aim of this study was to assess the influence of farmers` crop management practices on Striga infestation and maize grain yield. Sixty farmers` fields were randomly selected in nine communities across three savanna zones. About 35% of the farmers had cultivated their fields for over 10 years, 48% grew the Striga resistant variety 97 TZL Comp-1-W, 68% planted maize in mid-June and 60% practiced legume-maize rotation. About 33% intercropped maize + cowpea, 42% applied 100 kg N ha-1 and 87% conducted 2 to 3 hoe weedings. The Striga resistant maize variety reduced Striga count and host damage score and increased grain yield ha-1 in northern and southern Guinea savannas. However, the varieties grown in Sudan savanna increased Striga count ha-1 (R = 0.56**) and Striga damage (R = 0.59**) because they were not resistant to Striga. Planting maize in mid-July reduced Striga infestation in northern Guinea, but grain yield ha-1 was highest when maize was planted in mid-June in all three zones. Soybean-maize or groundnut-maize rotation reduced Striga count in all the agro-ecosystems. Relay intercropping of cowpea into maize reduced Striga count in northern Guinea. Higher nitrogen fertilizer rate reduced Striga count and score and significantly increased grain yield in the three zones. Two or three hoe weedings reduced Striga count in the three zones and Striga score in Sudan savanna. Thus, the farmers` practices sampled significantly influenced Striga infestation of maize fields in the three agro-ecosystems. The Striga resistant maize variety, Soybean-maize rotation, 100 kg N ha-1 and three hoe weedings could serve as component technologies in an integrated package for combating Striga menace in the region.